The Analysis of Differences in Financial Performance of Conventional Commercial Banks and Sharia Commercial Bank - Herlina, Sri; Gea, Iman Hati; Kaloeti, Ade Kristianus (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
The study aims to determine the difference in financial performance between Conventional Commercial Banks and Sharia Commercial Banks in Indonesia from 2015 to 2019. The financial ratios examined are CAR (Capital Adequacy Ratio), ROA (Return On Asset), ROE (Return On Equity), NPL (Non Performing Loan), LDR (Loan To Deposit Ratio). The population of conventional commercial banks is 96 banks and the population of Sharia commercial banks is 14 banks. After sampling with purposive sampling method, 11 conventional commercial banks and 11 Sharia commercial banks that meet the sampling criteria were obtained. This study used Kolmogrov Smirnov normality test analysis technique and independent sample t-test with the help of IBM SPSS Statistic 21. The result shows significant difference in finantial ratios between Conventional Commercial Banks and Sharia Commercial Banks in Indonesia from 2015 to 2019.